Desemprego e juventude: percepções dos jovens em um contexto neoliberal - Ferreira, Gabriel Ulbricht (Universidade Federal de São Carlos, 2023)
The increasing flexibility of labor relations, supported by the process of productive restructuring, led to an increase in job insecurity and unemployment, especially among younger people, a situation aggravated by the advent of neoliberalism as a dominant political and economic project. In addition, there is, in the current context, an ideological process, supported by neoliberal logic, which aims to justify and naturalize, through specific discourses and practices, a scenario of generalized uncertainties and insecurities, in which the subject himself is pointed out as the main responsible for his condition of unemployment. In this sense, this research sought to understand, based on a qualitative analysis, how the perceptions of unemployed young people about their condition (of unemployment) are articulated with current neoliberal discourses and practices, taking into account the experiences and references of these young workers, and observing how this condition impacts their subjectivity, their health and other spheres of their sociability. Thus, a case study was carried out from the Casa do Trabalhador in the municipality of São Carlos-SP, an institution that offers professional relocation services, including labor intermediation. The research was mainly conducted through interviews guided by a semi-structured script, in which it was possible to capture testimonials from twenty-two young unemployed people with the aim of understanding and relating them to the reality of the contemporary world of work, marked by in short, by precariousness and unemployment.
Unemployment and youth: perceptions of young people in a neoliberal context
Keywords: Trabalho; Desemprego; Empreendedorismo; Neoliberalismo; Ideologia; Juventude; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS